2019
DOI: 10.2174/1570159x17666190726115623
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Perspectives on DNA Double-strand Breaks in Neurodegenerative Diseases

Abstract: DNA double-strand breaks (DSBs) are common events that were recognized as one of the most toxic lesions in eukaryotic cells. DSBs are widely involved in many physiological processes such as V(D)J recombination, meiotic recombination, DNA replication and transcription. Deregulation of DSBs has been reported in multiple diseases in human beings, such as the neurodegenerative diseases, with which the underlying mechanisms are needed to be illustrated. Here, we reviewed the recent insights into the dysfunction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 125 publications
0
15
0
Order By: Relevance
“…Several studies have reported that DSB is augmented in AD brains 4 , 7 , 31 . First, we analyzed hippocampal slices of human AD brain and non-neurodegenerative disease control brain (Table 1 ) to pursue DSB in the AD brain by immunohistochemistry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that DSB is augmented in AD brains 4 , 7 , 31 . First, we analyzed hippocampal slices of human AD brain and non-neurodegenerative disease control brain (Table 1 ) to pursue DSB in the AD brain by immunohistochemistry.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, recent reports demonstrate that DSB accumulates in the hippocampus in the brains of AD patients and AD model mice 7 , 31 , 32 . Aβ-induced oxidative stress or activation of N-methyl-D-aspartate receptors (NMDARs) induces DSB 4 , 9 , 33 . Tau protein is almost exclusively localized to the axon, however, it is also reported to localize in the nucleus to stabilize DNA 34 38 .…”
Section: Introductionmentioning
confidence: 99%
“…The data suggest a strong link between DSBs, cancers, and neurodegenerative disorders, as well as several other diseases [9][10][11]. Genome-wide analysis of genes that are the main targets of DSBs was therefore important, including their roles in different biological processes and associations with diseases.…”
Section: Of 18mentioning
confidence: 99%
“…Next, we searched for possible associations of the genes subjected frequently to breakage with diseases. It was described previously that DSBs can lead to cancers and other diseases [9][10][11]. Nevertheless, the genome-wide identification and analysis of the The top ten Gene Ontology (GO) biological process associations of genes subjected to breakage were determined using Profiler (https://biit.cs.ut.ee/gprofiler/gost, accessed 28 June 2022).…”
Section: Associations Of the Genes That Are Targeted By Dsbs With Dis...mentioning
confidence: 99%
See 1 more Smart Citation